2018
DOI: 10.1016/j.cose.2018.07.011
|View full text |Cite
|
Sign up to set email alerts
|

A taxonomy of cyber-physical threats and impact in the smart home

Abstract: In the past, home automation was a small market for technology enthusiasts. Interconnectivity between devices was down to the owner's technical skills and creativity, while security was non-existent or primitive, because cyber threats were also largely non-existent or primitive. This is not the case any more. The adoption of Internet of Things technologies, cloud computing, artificial intelligence and an increasingly wide range of sensing and actuation capabilities has led to smart homes that are more practica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(71 citation statements)
references
References 68 publications
(91 reference statements)
1
53
0
1
Order By: Relevance
“…They referred to several types of attacks against these two protocols and detail on the ways such attacks can be addressed. After introducing a taxonomy of cyber-physical threats, the work in [92] examines a plethora of potential attacks in the smart home environment based on the presented taxonomy. The authors concentrated on both the attack vectors and the potential consequences on the systems and the occupants of such a house.…”
Section: Group IImentioning
confidence: 99%
“…They referred to several types of attacks against these two protocols and detail on the ways such attacks can be addressed. After introducing a taxonomy of cyber-physical threats, the work in [92] examines a plethora of potential attacks in the smart home environment based on the presented taxonomy. The authors concentrated on both the attack vectors and the potential consequences on the systems and the occupants of such a house.…”
Section: Group IImentioning
confidence: 99%
“…There are also studies that focused on building taxonomies for cyber-physical threats and attacks. In [12], Heartfield et al built a taxonomy for the cyber security threats that affect smart homes. In their taxonomy, they considered the impact on both the system and users.…”
Section: Selected Taxonomies In Cyber Securitymentioning
confidence: 99%
“…Therefore, a smart speaker can be a new target for an attacker to infiltrate into the smart home system. Heartfield et al [Heartfield, Loukas, Budimir et al (2018)] investigated and showed security threat taxonomy in a smart home. They enumerate possible attack vectors in the smart home system from a physical layer such as an infrared sensor and a voice to the application layer.…”
Section: Smart Home Securitymentioning
confidence: 99%